Investigation of drug release modulation from poly(2-oxazoline) micelles through ultrasound - Salgarella, Alice Rita; Zahoranová, Anna; Šrámková, Petra; Majerčíková, Monika; Pavlova, Ewa; Luxenhofer, Robert; Kronek, Juraj; Lacík, Igor; Ricotti, Leonardo (Scientific reports, 2018)
Among external stimuli used to trigger release of a drug from a polymeric carrier, ultrasound has gained increasing attention due to its non-invasive nature, safety and low cost. Despite this attention, there is only limited knowledge about how materials available for the preparation of drug carriers respond to ultrasound. This study investigates the effect of ultrasound on the release of a hydrophobic drug, dexamethasone, from poly(2-oxazoline)-based micelles. Spontaneous and ultrasound-mediated release of dexamethasone from five types of micelles made of poly(2-oxazoline) block copolymers, composed of hydrophilic poly(2-methyl-2-oxazoline) and hydrophobic poly(2-n-propyl-2-oxazoline) or poly(2-butyl-2-oxazoline-co-2-(3-butenyl)-2-oxazoline), was studied. The release profiles were fitted by zero-order and Ritger-Peppas models. The ultrasound increased the amount of released dexamethasone by 6% to 105% depending on the type of copolymer, the amount of loaded dexamethasone, and the stimulation time point. This study investigates for the first time the interaction between different poly(2-oxazoline)-based micelle formulations and ultrasound waves, quantifying the efficacy of such stimulation in modulating dexamethasone release from these nanocarriers.
Keywords: polymery; Polymers; Hydrophobic and Hydrophilic Interactions; Ultrasonics; dexamethason; Dexamethasone; Microscopy, Electron, Transmission; ultrazvuk; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; micely; lékové transportní systémy; Drug Delivery Systems; Drug Carriers; dynamický rozptyl světla; transmisní elektronová mikroskopie; Micelles; nosiče léků; hydrofobní a hydrofilní interakce; oxazoly; Dynamic Light Scattering; Oxazoles